Extracellular vesicles in liver disease and beyond - Morán, Laura (World J Gastroenterol, 2018)
Extracellular vesicles (EVs) are membrane-derived vesicles which can be released by different cell types, including hepatocytes, hepatic stellate cells and immune cells in normal and pathological conditions. EVs carry lipids, proteins, coding and non-coding RNAs and mitochondrial DNA causing modifications on the recipient cells. These vesicles are considered potential biomarkers and therapeutic agents for human diagnostic and prognostic due to their function as intercellular mediators of cell-cell communication within the liver and between other organs. However, the development and optimization of methods for EVs isolation is required to characterize their biological functions as well as their potential as a treatment option in the clinic. Nevertheless, many questions remain unanswered related to the function of EVs under physiological and pathological conditions. In the current editorial, the results obtained in different studies that investigated the role of intrahepatic EVs during liver diseases, including drug-induced liver injury, non-alcoholic fatty liver, non-alcoholic steatohepatitis, alcoholic liver disease and hepatocellular carcinoma and extrahepatic EVs in remote organs during pathological events such as pulmonary disease, cardiovascular diseases, neurodegenerative disorders e.g., Alzheimer’s disease, Parkinson’s disease and multiple sclerosis as well as in immunopathological processes, are discussed. Although much light needs to be shed on the mechanisms of EVs, these membrane-derived vesicles represent both a novel promising diagnostic, and a therapeutic tool for clinical use that we emphasize in the current editorial.